SEISMOGEOLOGY OF VERKHNEKERULEN BASIN (KHENTEI, NORTHERN MONGOLIA) - O. P. Smekalin; A. V. Chipizubov; V. S. Imaev (Геодинамика и тектонофизика)
The paper presents results of seismogeological studies of active faults bordering the Upper Kerulen basin, one of the largest intermountain basins of the Khentei upland. Morphometric and trenching methods were applied to estimate the main parameters of seismogenic dislocations and associated Holocene palaeoearthquakes (540–2810, 3170–3720, and 7480–9220 years ago). The maximum palaeoearthquake magnitude (7.5) characterizes the seismic capacity of the potential focal area (PFA) confined to the Kerulen fault. The new data show the need to revise the potential seismicity concepts of the southern Khentey area and to make appropriate changes in the general seismic zoning maps. The relationship between the dislocations and the modern topography features, as well as deformation of the subsurface sediments in the studied mine openings give evidence of thrusting under the sub-lateral to north-western subhorizontal compression.